VD_FINDINFO Jug / 2024 / 311 vom 29. November 2023 - VD Tribunal cantonal (2023)
PRÉSOMPTION D'INNOCENCE, APPRÉCIATION DES PREUVES, VIOLATION DES RÈGLES DE LA CIRCULATION, EXCÈS DE VITESSE | 106 CP, 34 CP, 42 al. 1 CP, 42 al. 4 CP, 44 al. 1 CP, 47 CP, 90 al. 2 LCR, 10 CPP (CH), 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)